2018
DOI: 10.1523/jneurosci.1397-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Tau Accumulation in Clinically Normal Older Adults Is Associated with Hippocampal Hyperactivity

Abstract: Animal studies demonstrate that hyperactive neurons facilitate early accumulation and spread of tau and amyloid-␤proteins in the pathological cascade of Alzheimer's disease (AD). Human neuroimaging studies have linked hippocampal hyperactivity to amyloid-␤ accumulation, apolipoprotein 4 (APOE4) and clinical progression from prodromal AD to clinical dementia. The relationship between hippocampal hyperactivity and early AD molecular pathology (amyloid-␤ and tau accumulation) before clinical symptoms remains to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 93 publications
13
62
0
Order By: Relevance
“…One possibility to reconcile the findings is that tau enhances amyloid-related neuronal hyperactivity at lower levels of amyloid, but reduces neuronal function at higher levels of amyloid. This stance would be in agreement with results from previous studies in humans reporting tau-PET but not amyloid-PET to be linked to fMRI-assessed hyperactivation [35] or FDG-PET hypermetabolism [15,16]. Furthermore, we observed FDG-PET hypermetabolism in the group of amyloid-negative/high-tau but not amyloid-positive/ low-tau suggesting that higher levels of tau in the presence of lower levels of amyloid are decisive for FDG-PET hypermetabolism.…”
Section: Discussionsupporting
confidence: 93%
“…One possibility to reconcile the findings is that tau enhances amyloid-related neuronal hyperactivity at lower levels of amyloid, but reduces neuronal function at higher levels of amyloid. This stance would be in agreement with results from previous studies in humans reporting tau-PET but not amyloid-PET to be linked to fMRI-assessed hyperactivation [35] or FDG-PET hypermetabolism [15,16]. Furthermore, we observed FDG-PET hypermetabolism in the group of amyloid-negative/high-tau but not amyloid-positive/ low-tau suggesting that higher levels of tau in the presence of lower levels of amyloid are decisive for FDG-PET hypermetabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, a reduced activity in this GABAergic population could promote hyperactivity in the entorhinal cortex and, consequently, hyperexcitability across the hippocampus . Interestingly, the hippocampal hyperactivity has also been associated with the spread of tau pathology before the clinical symptoms of AD .…”
Section: Discussionmentioning
confidence: 99%
“…Functional brain imaging studies in humans provide evidence that neuronal network hyperexcitability occurs in vulnerable brain regions early in the disease process and even before cognitive impairment is evident (Putcha et al, 2011;Huijbers et al, 2019). Studies of animal models of AD that exhibit A␤ and/or pTau pathology have consistently demonstrated hyperexcitabil-ity of neuronal circuits in the hippocampus and cerebral cortex (Verret et al, 2012;Martinez-Losa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%